Can adjuvant immune checkpoint inhibitors improve the long-term outcomes of hepatocellular carcinoma with high-risk recurrent factors after liver resection? A meta-analysis and systematic review - Hu, Lingbo; Kong, Yenan; Qiao, Yingli; Wang, Aidong (Frontiers in Oncology, 2024)
Background: Administering adjuvant therapy following liver resection is crucial for patients with hepatocellular carcinoma (HCC) exhibiting high-risk recurrence factors.Immune checkpoint inhibitors (ICIs) are effective against unresectable HCC; however, their effectiveness and safety for this specific patient group remain uncertain.Methods: We conducted an extensive literature search across four scholarly databases to identify relevant studies. Our primary endpoints were overall survival (OS), recurrence-free survival (RFS), and adverse events (AEs). OS and RFS were quantified using hazard ratios (HRs), whereas the 1-, 2-, and 3-year OS and RFS rates were expressed as risk ratios (RRs). Additionally, the incidence of AEs was calculated.Results: Our meta-analysis included 11 studies (N = 3,219 patients), comprising two randomized controlled trials (RCTs) and nine retrospective studies. Among these, eight studies reported HRs for OS, showing a statistically significant improvement in OS among patients receiving adjuvant ICIs (HR, 0.60; 95% confidence interval [CI], 0.45-0.80; p < 0.0001). All included studies reported HRs for RFS, indicating a favorable impact of adjuvant ICIs (HR, 0.62; 95% CI, 0.52-0.73; p < 0.0001). Moreover, aggregated data demonstrated improved 1-and 2-year OS and RFS rates with adjuvant ICIs. The incidence rate of AEs of any grade was 0.70 (95% CI, 0.49-0.91), with grade 3 or above AEs occurring at a rate of 0.12 (95% CI, 0.05-0.20).Conclusion: Adjuvant ICI therapy can enhance both OS and RFS rates in patients with HCC exhibiting high-risk recurrence factors, with manageable AEs.